تداعيات عدم الاستقرار السياسي والأمني في السودان على الأمن القومي الليبي في ظل تصاعد التهديدات العابرة للحدود (Comprehensive Journal of Science, 2026)
This study summary presents an analytical investigation of the impact of political and security instability in Sudan on Libyan national security, emphasizing cross-border security threats resulting from ongoing armed conflicts, proliferation of armed groups, arms and drug trafficking, and irregular migration. The study aims to establish a clear understanding of the causal links between the Sudanese conflict and Libya’s national security, providing an in-depth evaluation of current and potential threats, while proposing strategies to enhance border security and regional cooperation.The research employs a descriptive-analytical approach, systems analysis, and content analysis methodologies, ensuring a scientific and comprehensive examination of the mechanisms through which threats traverse national borders. It draws extensively on previous studies, scholarly publications, official reports by the United Nations, regional analysis reports, and credible news agency coverage, integrating both theoretical and practical perspectives.Findings from previous research indicate that Libya’s national security is directly influenced by instability in Sudan, with consequences including the spread of armed groups, increased cross-border trafficking, and irregular migration pressures, which collectively exacerbate security vulnerabilities. These insights underscore the critical need for proactive regional security measures, integrated monitoring systems, and enhanced cooperation between Libya and neighboring states.The study concludes that securing Libya’s national interests requires comprehensive mechanisms to monitor cross-border threats, strengthen border control institutions, and coordinate with regional and international partners, thereby maintaining national stability. Moreover, this research provides a robust analytical framework that can guide future studies on the effects of internal conflicts on regional security dynamics, particularly within North Africa and the Sahel region.